2016
DOI: 10.21107/agriekonomika.v5i1.1035
|View full text |Cite
|
Sign up to set email alerts
|

Tingkat Konsistensi Pemuda Tani Terhadap Transformasi Sektor Pertanian Di Kabupaten Ponorogo

Abstract: <p>Sebagai salah satu daerah di propinsi Jawa Timur yang menyumbang devisa terbesar di Indonesia melalui pengiriman TKI di luar negeri adalah kabupaten Ponorogo. Fenomena tersebut menyebabkan adanya permasalahan tata keruangan wilayah maupun sosiologi pedesaan .Hal ini memberikan dampak pada pergeseran mata pencaharian dari petani menjadi bukan petani. Salah satu wilayah yang mengalami perubahan menjadi perkotaan adalah di lima desa Kabupaten Ponorogo yaitu Mojorejo, Kemuning, Siwalan, Babadan, Demangan … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 0 publications
0
5
0
4
Order By: Relevance
“…With this optimism to empower the young generation of agriculture to be able to bring change and progress in food crop agriculture. (Arvianti, Asnah & Prasetyo 2015) also found that continuous encouragement to the young generation of agriculture in developing consistent food crop farming, increased understanding in agriculture and active participation in agricultural extension activities would contribute to food security.…”
Section: The Influence Of Hr Characteristics On the Work Preferences ...mentioning
confidence: 99%
See 1 more Smart Citation
“…With this optimism to empower the young generation of agriculture to be able to bring change and progress in food crop agriculture. (Arvianti, Asnah & Prasetyo 2015) also found that continuous encouragement to the young generation of agriculture in developing consistent food crop farming, increased understanding in agriculture and active participation in agricultural extension activities would contribute to food security.…”
Section: The Influence Of Hr Characteristics On the Work Preferences ...mentioning
confidence: 99%
“…Parents' income from farming could also affect the interest of young people to want or not to continue family farming (Arimbawa & Rustariyuni 2018). Youth who had an interest in business see the prospect of profit so that income became the main consideration (Arvianti et al 2015); (Oktaviani, Usman & Azhar 2017). Therefore, if the income in the agricultural sector was high and economically profitable it would foster the interest of young farmers to be involved in the agricultural sector, and vice versa and support from the family and the surrounding community was very important because it could affect the interest of young people to farm (Oktaviani et al 2017).…”
Section: The Influence Of Hr Characteristics On the Work Preferences ...mentioning
confidence: 99%
“…Dengan ini optimisme untuk memberdayakan generasi muda pertanian agar mampu membawa perubahan dan kemajuan dalam pertanian tanaman pangan. Arvianti (2016)jugamenemukan bahwa dorongan yang terus-menerus kepada generasi muda pertanian untuk mengembangkan usahatani tanaman pangan yang konsisten, peningkatan pemahaman di bidang pertanian serta partisipasi aktif dalam kegiatan penyuluhan pertanian akan berkontribusi pada ketahanan pangan.…”
Section: Pendahuluanunclassified
“…To realize those things (Sumastuti, 2010) explains that good synergy between natural, physical and human resource factors are needed, including land ownership structure, availability of production facilities, human resources and institutions. However, one of the problems of agricultural development in Indonesia is Human Resource (HR) issues such as the lack of ability of farmers, breeders, and planters to utilize advanced technology; limited instructors, and the lowest interest of younger generation to engage in agriculture (Arvianti, et al, 2015).…”
Section: Introducingmentioning
confidence: 99%